Phytochemical Profiling of Gynura procumbens (Lour.) Merr. Leaves and Stem Extracts Using UHPLC-Q-Orbitrap HRMS - Dewi Anggraini Septaningsih; Cecep Abdurohman Putra; Irma Herawati Suparto; Suminar Setiati Achmadi; Rudi Heryanto; Mohamad Rafi (Universitas Gadjah Mada, 2022)
In Indonesia, Gynura procumbens (Lour.) Merr., known as Longevity Spinach or Sambung Nyawa, is commonly grown in tropical and subtropical Asian countries. Many biological activities of G. procumbens have been reported. As we know, the composition and concentration of metabolites, as well as plant parts will significantly affect the biological activities. In this work, UHPLC-Q-Orbitrap-HRMS was used for the putative identification of metabolites present in 70% ethanol extract of G. procumbens leaves and stem extract. Also, we performed clustering of G. procumbens leaves and stem extracts using principal component analysis (PCA) with the peak area of the identified metabolites as the variable. Thirty-one metabolites were identified, and the number of identified peaks in the leaves is higher than in the stem. Those identified metabolites are phenolics, fatty acids, oxo monocarboxylic acids, porphyrins, and chlorophyll fragments. The PCA results showed that the leaves and stem extracts could be grouped, indicating that the composition and concentration of detected compounds differed.